(untitled) (Research, Society and Development, 2021)
Objective: To understand the representations of nursing students about sexuality and gender. Methodology: We chose a qualitative study, based on the Theory of Social Representations (RS). The target population of the research was composed by students of the Nursing Course of the Federal University of Campina Grande (UFCG). The IRaMuTeQ software version 0.7 Alpha 2 was used to aid in the organization of the data. The analysis was based on content analysis. Results: The representations of the students were different due to the period of the course, especially when related to the notions about the body and care within the scope of Nursing. Three analytical categories emerged: (1) Sexuality and gender: recognizing the weaknesses of the training process; (2) Pointed insecurities; (3) Need for other paths. Discussion: The discourses of the students revealed a fragility in the formative process regarding the absence of practices and discussions that involved the diversity of gender and sexuality. Conclusion: It is proposed to implement the theme inside and outside the classrooms, allowing the Nursing student to reflect and experience issues inherent to sexuality and gender as dimensions of human life.